Personalizing Research: Special Educators' Awareness of Evidence-Based Practice. Issue 2 (2nd April 2016) - Guckert, Mary; Mastropieri, Margo A.; Scruggs, Thomas E.
ABSTRACT: Although evidence-based practices are considered critical to student success, a research-to-practice gap exists. This qualitative study examined practicing special education teachers' perceptions of their use of evidence-based practices. Special education teachers were interviewed and their classroom practices examined. Major themes emerged and findings revealed that (a) teachers believe they are using evidence-based practices, (b) teachers' awareness of research varies, and (c) teachers' personalization of research varies by awareness level. Awareness levels of credible evidence-based practices ranged from Aware, Partially Aware, and Unaware. Sources of evidence varied greatly from university coursework, research articles, co-workers' ideas, and self-generated ideas. Personalization of evidence-based practices consisted of teachers adapting and modifying practices to meet their own needs, rather than relying on fidelity of treatment measures. Implications for the special education classroom are discussed.